(untitled) (Acta Polytechnica CTU Proceedings, 2022)
The climatic data on which the current generation of the Eurocodes are based are mostly about 20 years old, with some exceptions of recent updates at a national level. The second generation of the Eurocodes for structural design is expected to be nationally implemented within next few years and operational National Annexes should be subsequently developed and the climatic maps revised. Some models for extreme climate actions are still missing within Eurocodes including wind action effects due to non-synoptic storms, which are common in most of the world and are of increasing importance in Europe. The aim of this contribution is to analyse how the impact of anticipated changes in European climate could affect the assessment of design weather parameters, including the partial factor design approach for structures according to Eurocodes, based on current knowledge concerning projection models of future climate in Europe.